Potential of Neuraminidase from Pasteurella multocida for Inhibiting Avian Influenza Virus Subtype H9N2 Replication In Ovo - Poetri, O. N.; Nugroho, C. M. H.; Silaen, O. S. M.; Kurnia, R. S.; Krisnamurti, D. G. B.; Indrawati, A.; Hikmah, N.; Hariyadi, I. P. P. K.; Putra, M. A.; Soebandrio, A. (Tropical Animal Science Journal, 2023)
In recent decades, neuraminidase/sialidase-based antivirals have been produced to suppress respiratory viral infections, including avian influenza, which relies on sialic acid as the entry point for viruses into cells. While neuraminidase has been extensively studied as an antiviral agent, numerous neuraminidases still have not been evaluated for their antiviral activities. Among these is NanB neuraminidase derived from Pasteurella multocida, which has received limited research attention. This study aimed to assess the potential of NanB neuraminidase in inhibiting H9N2 avian influenza virus infection in ovo. The research commenced with the molecular re-identification of the H9N2 A/Layer/Indonesia/WestJava-04/17 virus isolate, followed by determining the EID50 through Rapid HA test results. The toxicity of NanB neuraminidase was assessed by administering various doses to embryonated chicken eggs (ECE). The antiviral activity of NanB neuraminidase on ECE was evaluated through challenge tests, including treatment before, during, and after the challenge. The assessment involved monitoring the time of embryo death, virus titer through HA test, and viral copy number via RT-qPCR. The results indicated that the H9N2 virus titers capable of infecting 50% of ECE amounted to 108.83 EID50/mL. A dose of 0.258 U/mL of NanB neuraminidase was found to be toxic, leading to embryo mortality after 48 hours of incubation at 37 ℃, while a non-toxic dose was determined to be 0.129 U/mL. The post-challenge treatment group exhibited the most significant reduction in virus titer in ECE. Notably, NanB neuraminidase derived from P. multocida demonstrated the ability to inhibit H9N2 avian influenza virus infection in the ovo model, with the optimal dosage of 0.129 U/mL. The observed decrease in virus titers in the hemagglutination assay and viral copy number assays suggests that NanB neuraminidase holds promise as a potential antiviral candidate for therapeutic approach.